Colorless Tsukuru Tazaki and his years of pilgrimage [compact disc, unabridged] : a novel - Murakami, Haruki, 1949- (Books on Tape : Random House Audio, 2014)
Tsukuru Tazaki's life was irreparably changed when his relationships with his high school best friends became severed during Tsukuru's college days. Now at 35, Tsukuru's girlfriend Sara suggested to Tsukuru to go and talk to these high school friends in person to mend the relationships, and to discover the real reason behind the friends' decision to reject Tsukuru. Tsukuru visited his friends in Nagoya and Finland one by one, and uncovers the real reason as to why their relations were broken off.